NILAI DIAGNOSTIK SKOR STROKE DAVE UNHAS PADA PENDERITA STROKE ISKEMIK KARDIOEMBOLI DENGAN FIBRILASI ATRIUM - Supardin Supardin; David Gunawan; Cahyono Kaelan (PERDOSNI, 2019)
DIAGNOSTIC VALUE OF DAVE UNHAS STROKE SCORE IN CARDIOEMBOLIC ISCHEMIC STROKE PATIENTS WITH ATRIAL FIBRILLATIONABSTRACTIntroduction: It is important to diagnose cardioembolic ischemic stroke quickly especially in the absence of CT scan/MRI, besides having a poor prognosis, cardioembolic ischemic stroke also has high disability and death rates.Aim: To investigate the diagnostic value of Dave Unhas Stroke Score (DUSS) in cardioembolic ischemic stroke patients with atrial fibrillation (AF).Methods: This was a diagnostic test research on cardioembolic ischemic stroke sufferers with AF and without cardioemboli in Wahidin Sudirohusodo Hospital and its networking hospital in Makassar from September 2018 to March 2019. DUSS consists of 5 variables: blood pressure (BP), activity at onset, headache, vomiting, and level of consciousness were assessed in both groups. DUSS cut off point was determined by receiver operating characteristics (ROC). The test results are considered as statistically significant if the p value <0.05.Results: There were 80 subjects consisting of 40 subjects each in the cardioembolic and noncardioembolic ischemic stroke groups. The research results showed diagnostic value of DUSS in cardioembolic ischemic stroke patients due to atrial fibrillation with cut off point 10 had a sensitivity of 95.0%, specificity 97.5%, positive predictive value 97.4%, negative predictive value 95.1%, and accuracy 96.2%. The results of this calculation shown area under curve (AUC) on the ROC curve that is 99.6% with a very significant p value (p <0.001) which means DUSS can be used to distinguish between cardioembolic ischemic stroke due to AF (score >10) from noncardioembolic ischemic stroke (score <10).Discussion: DUSS 10 cut off point can distinguish cardioembolic ischemic stroke due to AF and noncardioembolic.Keywords: Dave Unhas Stroke Score, cardioembolic ischemic stroke patients with atrial fibrillation, noncardioembolic ischemic stroke, diagnostic value, cut-off pointABSTRAKPendahuluan: Mendiagnosis stroke iskemik kardioemboli dengan cepat penting dilakukan terutama pada keadaan tidak tersedianya CT scan/MRI, selain karena memiliki prognosis yang buruk, juga memiliki angka kecacatan dan kematian yang tinggi.Tujuan: Mengetahui nilai diagnostik Skor Stroke Dave Unhas (SSDU) pada penderita stroke iskemik kardioemboli akibat fibrilasi atrium (FA).Metode: Penelitian uji diagnostik terhadap penderita stroke iskemik kardioemboli dengan FA dan nonkardioemboli di RS Wahidin Sudirohusodo dan jejaringnya di Makassar pada bulan September 2018-Maret 2019. Dilakukan penghitungan SSDU berdasarkan 5 variabel: tekanan darah (TD), aktivitas saat serangan, nyeri kepala, muntah, dan tingkat kesadaran pada kedua kelompok serta cut off point SSDU yang optimal menggunakan receiver operating characteristics (ROC). Hasil uji statistik signifikan jika nilai p<0,05.Hasil: Didapatkan 80 subjek yang terdiri dari masing-masing 40 subjek pada kelompok stroke iskemik kardioemboli dan nonkardioemboli. Hasil penelitian menunjukkan nilai diagnostik SSDU pada penderita stroke iskemik kardioemboli akibat FA dengan cut off point 10 memiliki sensitivitas 95,0%, spesifisitas 97,5%, nilai prediksi positif 97,4%, nilai prediksi negatif 95,1%, dan akurasi 96,2%. Hasil perhitungan ini menunjukkan area under curve (AUC) pada kurva ROC, yaitu 99,6% dengan nilai p yang sangat signifikan (p<0,001) yang berarti SSDU dapat digunakan untuk membedakan antara SIkardioemboli akibat FA (skor >10) dengan stroke iskemik nonkardioemboli (skor <10).Diskusi: Diperoleh cut off point SSDU 10 yang dapat membedakan stroke iskemik kardioemboli akibat FA dan nonkardioemboli.Kata kunci: Fibrilasi atrium, kardioemboli, nonkardioemboli, nilai diagnostik, stroke iskemik, Skor Stroke Dave Unhas